Transformasi Lanskap Agraris dan Ekspansi Lahan Terbangun: Dinamika Spasio-Temporal Indeks Kawasan Terbangun (NDBI) Berbasis Landsat Time-Series di Jember Selatan, 2001–2025: Agrarian Landscape Transformation and Built-Up Area Expansion: Spatio-Temporal Dynamics of the Built-Up Area Index (NDBI) Based on Landsat Time-Series in South Jember, 2001–2025 - Rizqi I’anatus Sholihah; Rizki Auliansyah Putra; Muflihatul Maghfiroh Islami; Krisologus Genesa Ruby Atmadja; Lenalda Febriany Santosa; Verlina Intan Wulandari; Basuki Rahman; Monica Kusneti (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Agrarian landscape transformation driven by built-up land expansion has become an increasingly prominent form of land-use change in developing regions. Southern Jember, characterized by extensive agricultural, plantation, and forested lands, has experienced growing development pressure associated with infrastructure expansion and regional economic growth. This study aimed to analyze patterns of agrarian landscape transformation and the spatio-temporal dynamics of built-up areas in Southern Jember during 2001–2025 using Landsat time-series imagery. The analysis was conducted through land-cover change interpretation and the extraction of the Normalized Difference Built-up Index(NDBI) from Landsat 7 ETM+ and Landsat 8 OLI/TIRS imagery. The results revealed a substantial increase in built-up areas, from approximately 20.8 thousand ha in 2001 to 82.9 thousand ha in 2025. This expansion occurred concurrently with declines in paddy fields, secondary forests, and portions of plantation areas. NDBI analysis further indicated increasing intensity and spatial expansion of built-up land, particularly along the northern, central, and western development corridors of Southern Jember, where high NDBI values were consistently observed. These findings demonstrate that built-up land expansion has become the primary driver of agrarian landscape transformation in the study area. The integration of Landsat time-series imagery and NDBI proved effective for monitoring landscape dynamics and provides a scientific basis for sustainable spatial planning and land management.